Pengaruh Promosi Perpustakaan Melalui Instagram Terhadap Pemanfaatan Layanan di Library and Knowledge Center Binus @Senayan kampus - Arief, Noor; Maulidya, Bella Septi (Jurnal FPPTI, 2023)
This study seeks to determine the impact of Instagram promotion on using Library and Knowledge Centre (LKC) Binus @Senayan Campus services. Using a quantitative descriptive method, the author defines the population as the number of visitors, lecturers, and students who come to the LKC Binus @ Senayan Campus, totaling 198 people (from 01 January 2021 to 20 May 2022), while the research sample is 5% of the entire population—comprising 133 individuals. The author collected samples using the Accidental Sampling technique. In other words, respondents are selected arbitrarily or not beforehand. In this study, the dependent variable is library users, and the independent variable is Instagram. The utilization of a library is measured using indicators such as service quality, including concrete evidence, dependability, responsiveness, assurance, and empathy. Indicators such as the implementation of promotions, promotional media, and promotional periods can be used to determine the degree to which a library is promoted on Instagram. According to the investigation conducted, the value was 21.356>1.97824. This indicates that tcount is a more significant value than the t table, positively affecting the utilization of services at the LKC Binus @Senayan Campus. In addition, the significance level is 0.0000.05, indicating that the influence of promotion on the use of services at the LKC Binus @Senayan Campus is significant. Based on the findings of this study, it can be concluded that Instagram promotion has a positive and significant effect on the LKC Binus @Senayan Campus's service utilization.